High-resolution electron energy loss spectroscopy of anions chemisorbed on electrode surfaces: The effect of counter cations - Baricuatro, Jack H.; Soto, José C.; Cummins, Kyle D.; Soriaga, Manuel P. (Electrochemistry communications, 2013)
In the course of experiments that included Auger electron spectroscopy (AES) and high-resolution electron energy loss spectroscopy (HREELS) on cation exchange at benzoquinone sulfonate chemisorbed on a Pd(111) electrode, it was found that, whereas the AES spectra remained invariant as the counter cation was varied from H+ to K+ to Cs+, profound changes occurred in the HREELS spectra. Specifically, the intensity of the spectral features decreased noticeably when H+ was replaced with K+. And, when the K+ ions were exchanged with Cs+, nothing but a flat-line (dead) spectrum was observed; even the elastic peak was completely attenuated. When the Cs+ ions were displaced by protons, the initial undiminished spectrum was fully restored. This outcome, while unrelated to cation-exchange selectivity, is of exceptional significance in surface electron spectroscopy. It appears that the positive ions on the surface attracted the low-energy incident electrons such that backscattering towards the energy analyzer was hindered; partially by K+ but totally by the larger Cs+ ion. The use of HREELS to examine the molecular integrity of chemisorbed anionic species must thus take cognizance of the possibility that the counter cation chosen to preserve interfacial-layer electroneutrality can have a profound effect. To circumvent such complication, low-valent and small-radii cations will have to be employed. In addition, although subject to instrument limitations, higher incident-electron energies could be adopted. AES, with incident-electron energies in the kV range, is impervious to the presence of counter cations. [Display omitted] ► We examine, by HREELS, cation-exchange at a surface with chemisorbed anionic species. ► The HREELS spectra are affected by the presence of counter cations. ► The larger the counter cation, the more profound the influence. ► The HREELS features, even the elastic peak, are completely suppressed by Cs cations.